Subsequent Acupuncture Reverses the Aftereffects of Intermittent Theta-Burst Stimulation - He, Xiao-Kuo; Liu, Hui-Hua; Chen, Shan-Jia; Sun, Qian-Qian; Yu, Guo; Lei, Lei; Niu, Zhen-Yuan; Chen, Li-Dian; Hsieh, Tsung-Hsun (Frontiers in Neural Circuits, 2021)
Objective: This study explored whether acupuncture affects the maintenance of long-term potentiation (LTP)-like plasticity induced by transcranial magnetic stimulation (TMS) and the acquisition of motor skills following repetitive sequential visual isometric pinch task (SVIPT) training. Methods: Thirty-six participants were recruited. The changes in the aftereffects induced by intermittent theta-burst stimulation (iTBS) and followed acupuncture were tested by the amplitude motor evoked potential (MEP) at pre- and post-iTBS for 30 min and at acupuncture-in and -off for 30 min. Secondly the effects of acupuncture on SVIPT movement in inducing error rate and learning skill index were tested. Results: Following one session of iTBS, the MEP amplitude was increased and maintained at a high level for 30 min. The facilitation of MEP was gradually decreased to the baseline level during acupuncture-in and did not return to a high level after needle extraction. The SVIPT-acupuncture group had a lower learning skill index than those in the SVIPT group, indicating that acupuncture intervention after SVIPT training may restrain the acquisition ability of one’s learning skills. Conclusion: Acupuncture could reverse the LTP-like plasticity of the contralateral motor cortex induced by iTBS. Subsequent acupuncture may negatively affect the efficacy of the acquisition of learned skills in repetitive exercise training.